Differential Expression Characterisation of the Heat Shock Proteins DnaJB6, DnaJshv, DnaJB13, and DnaJB14 in Apis cerana cerana Under Various Stress Conditions - Li, Guilin; Zhang, Shuxin; Wang, Hongfang; Liang, Li; Liu, Zhenguo; Wang, Ying; Xu, Baohua; Zhao, Hang (Frontiers in Ecology and Evolution, 2022)
As key pollinators, bees are frequently exposed to multiple environmental stresses and have developed crucial mechanisms by which they adapt to these stressors. However, the molecular bases mediated at the gene level remain to be discovered. Here, we found four heat shock protein DnaJB subfamily genes, DnaJB6, DnaJshv, DnaJB13 and DnaJB14, from Apis cerana cerana, that all have J domains in their protein sequences. The expression levels of DnJB6 and DnaJshv were upregulated by different degrees of heat stress, and the transcript level of DnaJB14 was gradually upregulated as the degree of heat stress increased, while the mRNA level of DnaJB13 was downregulated at multiple time points during heat stress treatment. The mRNA levels of all four DnaJBs were upregulated by cold and UV stress. In addition, the expression levels of DnaJB6, DnaJshv and DnaJB13 were reduced under abamectin, imidacloprid, cypermethrin, bifenthrin, spirodiclofen and methomyl stresses. The transcript level of DnaJB14 was decreased by imidacloprid, cypermethrin, spirodiclofen and methomyl exposure but increased by abamectin and bifenthrin exposure. These results indicate that the demand of A. cerana cerana for these four DnaJBs differs under various stress conditions. To further explore the role of DnaJBs in the stress response, we successfully silenced DnaJshv and DnaJB14. The content of protein carbonyl was increased, while the content of VC, the enzymatic activities of CAT, GST and SOD, the mRNA levels of many antioxidant-related genes, and the total antioxidant capacity were reduced after knockdown of DnaJshv and DnaJB14 in A. cerana cerana. These results indicate that silencing DnaJshv and DnaJB14 increases oxidative damage and decreases the antioxidant ability of A. cerana cerana. Taken together, our results demonstrate that DnaJB6, DnaJshv, DnaJB13 and DnaJB14 are differentially expressed under stress conditions and play crucial roles in response to various stressors, possibly through the antioxidant signalling pathway. These findings will be conducive to understanding the molecular basis of bee responses to environmental stresses and are beneficial for improving bee protection.